The effects of N-acetyl cysteine on bacterial translocation after pneumoperitoneum - Ilhan, YS; Altas, O (Medimond Publishing Co, 2004)
24 Wistar Albino rats were divided into 3 group. Group 1 no process was applicated. Group 2 saline solution was given via orally and Group 3 N-acetyl cysteine was given intraperitonally during 3 days. E.coli (10(10)/1) were given orally to the all subjects. Pneumoperitoneum was constituted (20 mmHg, CO2, 1 hour) in group 2 and 3. Translocation of E.coli was investigated in polimerase chain reaction, mesenteric lymph nodes and spleen. NO, MDA,SOD and GSH-Px enzyme were studied in serum. Terminal ileum were evaluated histopathologically. Bacterial translocation and free oxygene radicals levels increased in Group 2 compared to Group1. Decreased bacterial translocation and free oxygene radicals levels however increased activities of enzymes were found in group 3 compared to Group 2 but histological cellular damage persisted by decreasing. We suggested that N-acetyl cysteine reduce the bacterial translocation and the formation of free oxygene radicals after pneurnoperitoneum, and prevent the cellular damage.
39th Congress of the European-Society-for-Surgical-Research -- MAY 12-15, 2004 -- Athens, GREECE
Keywords: Carbon-Dioxide; Insufflation; Ischemia; Gut